How to improve emotional regulation in breast cancer survivors? A psychological intervention - Sebri, Valeria; Policardo, Giulia Rosa; Pravettoni, Gabriella (Frontiers in Psychology, 2024)
Objective: Psychological interventions are pivotal in enhancing the Quality of Life for breast cancer survivors, with a primary focus on addressing affective and cognitive challenges through group discussions among those diagnosed with the disease. While the influence of Body Image on overall well-being is well-documented, research on interventions specifically designed to address Body Image concerns in this demographic remains scarce. The present study aimed to fill this gap by evaluating the outcomes of a psychological intervention focused on fostering a positive Body Image among 25 breast cancer survivors. Method: Participants were divided into an experimental group, which received the intervention (n=13), and a control group that did not receive any psychological support (n=12). Results: Our findings highlight significant disparities in emotional regulation strategies, specifically cognitive reappraisal and expressive suppression, with the intervention group reporting enhanced emotional regulation. Contrary to initial hypotheses, the analysis unveiled statistically significant differences in both negative (social physique anxiety) and positive (functionality appreciation) body image dimensions, indicating elevated levels of social physique anxiety and reduced functionality appreciation among intervention participants. Conclusions: The total results may suggest that the intervention, while effective in enhancing emotional regulation, heightened awareness of body image issues, leading to increased social physique anxiety and diminished functionality appreciation. The paper further discusses practical implications arising from these insights.